An examination of the joint effects of adolescent interpersonal styles and parenting styles on substance use. (15th August 2022) - Meisel, Samuel N.; Colder, Craig R.
Abstract: The current study examined how parenting and adolescent interpersonal styles jointly influence youths' abilities to form close relationships – a central developmental milestone – yet avoid substance use, which predominantly occurs in the presence of peers. Nine annual waves from an adolescent sample ( N = 387) were used to assess (a) combinations of interpersonal and parenting styles from early to middle adolescence using longitudinal latent profile analysis, (b) the validity of these profiles on indicators of adjustment, and (c) the relationships between the profiles and growth in substance use across adolescence as well as substance-related consequences in late adolescence. The results supported five distinct combinations of interpersonal and parenting styles, and validity analyses identified both risk and protective profiles. The protective profile submissive–communal interpersonal style + high-warmth–authoritative parenting style was associated with indicators of positive social adjustment (e.g., friendship quality, resistance to peer influence) as well as lower levels of substance use. Significant differences also emerged with respect to substance-related consequences. The findings of this study highlight how combinations of adolescent interpersonal style and parenting render adolescents more or less successful at navigating peer relationships while avoiding substance use behaviors.